Human aging magnifies genetic effects on executive functioning and working memory - Nagel, Irene E.; Chicherio, Christian; Li, Shu-Chen; Von Oertzen, Timo; Sander, Thomas; Villringer, Arno; Heekeren, Hauke R.; Bäckman, Lars; Lindenberger, Ulman (Frontiers in Human Neuroscience, 2008)
We demonstrate that common genetic polymorphisms contribute to the increasing heterogeneity of cognitive functioning in old age. We assess two common Val/Met polymorphisms, one affecting the Catechol-O-Methyltransferase (COMT) enzyme, which degrades dopamine (DA) in prefrontal cortex (PFC), and the other influencing the brain-derived neurotrophic factor (BDNF) protein. In two tasks (Wisconsin Card Sorting and spatial working memory), we find that effects of COMT genotype on cognitive performance are magnified in old age and modulated by BDNF genotype. Older COMT Val homozygotes showed particularly low levels of performance if they were also BDNF Met carriers. The age-associated magnification of COMT gene effects provides novel information on the inverted U-shaped relation linking dopaminergic neuromodulation in PFC to cognitive performance. The modulation of COMT effects by BDNF extends recent evidence of close interactions between frontal and medial-temporal circuitries in executive functioning and working memory.